"Solar-Powered Pneumatic-Operated Can Crusher " Arabela Joy T. Deduyo... et al ... - Arabela Joy T. Deduyo; Joedel R. Llana; Noemi Regine P. San Jose; Jessielyn T. Santos; Victorio, Ver Ian J. (2024)
Generally, this study aimed to develop a solar-powered pneumatic-operated can crusher. Specifically, this study sought to design and fabricate a solar-powered pneumatic-operated can crusher. It evaluated the effectiveness of the developed solar-powered pneumatic-operated can crusher in terms of functional suitability, performance efficiency, reliability, safety, and maintainability. It also evaluated the crushed cans produced by the developed solar-powered pneumatic-operated can crusher in terms of acceptability and efficiency of transfer. The developed solar-powered pneumatic-operated can crusher was evaluated by 31 individual respondents, consisting of fifteen (15) junkshops which are the end-users, six (6) experts from the Waste Management Sectors and Licensed Mechanical Engineers, and ten (10) can manufacturers. In guiding the research in attaining the intended objectives, descriptive and developmental research methods were considered. The developed can crusher consists of solar and pneumatic mechanisms and was evaluated through a researcher-modified questionnaire. The evaluation was based on a researcher-modified survey questionnaire using ISO/IEC 25010 standards. The can crusher has a length of 76.2 cm, width of 152 cm, and a height of 122 cm. The can crusher used a 250W solar panel and two 12V batteries for the solar-powered crushing process, and it also uses power from electrical outlets. The developed solar-powered pneumatic-operated can crusher was operated by a sensor to detect aluminum cans and their levels if they reached maximum capacity inside the trash bin. The developed can crusher has two chambers for optimal performance. The programmed pneumatic system$1 (Bcylinder, valve, sensor, and control system$1 (Benables precise automated crushing process control in the upper part of the compartment. To crush cans safely and effectively, this pneumatic system applies force. The pneumatic system compressor and crushed can bin are in the lower compartment. The respondents rated the developed can crusher as "Highly Acceptable" with regard to functional suitability, performance efficiency, reliability, safety, and maintainability, as determined by the evaluation results. Based on the results of the evaluation of acceptability of crushed cans, the cans were squeezed from their original cylindrical shape to a flat, compact form, demonstrating the effectiveness and efficiency of the crushing process. This transformation not only displays the effectiveness of pneumatic operation in lowering can volume, but it also highlights the crusher's ability to prepare cans for recycling. The flattened cans not only save space but also improve recycling operations by improving storage and transporting more than the usual quantity. The researchers developed a user$1 (Bs manual for the Solar-Powered Pneumatic-Operated Can Crusher. The user$1 (Bs manual helps users become familiar with the machine in various aspects. This study also concluded that the manual consists of a machine overview, specification of pneumatic can crusher, safety precautions for solar panel and system, safety precautions for pneumatic can crusher, operating instructions, and maintenance. The findings revealed that the can crusher satisfies the respondents' expectations with regard to functional suitability, performance efficiency, dependability, safety, and maintenance, as well as the acceptability and transfer efficiency of the crushed cans. The solar-powered pneumatic can crusher that was developed received a "Highly Acceptable" rating across several parameters, including functional suitability, performance efficiency, reliability, safety, maintainability, acceptability of the crushed cans, and transfer efficiency. The researchers recommend further study to attain a more convenient and effective way to balance energy efficiency and space utilization in the solar-powered pneumatic can crusher. Another recommendation is for future researchers to design and develop a can crusher with a larger compressor to increase airflow and pressure, resulting in more effective metal can crushing. They also suggest including an exhaust system for heat reduction and four lockable wheels for portability and stability as appropriate features for the can crusher.s
Thesis